Formulation and Characterization of Drug Loaded Nonionic Surfactant Vesicles (Niosomes) for Oral Bioavailability Enhancement - Sunil Kamboj; Vipin Saini; Suman Bala (The Scientific World Journal)
Nonionic surfactant vesicles (niosomes) were formulated with an aim of enhancing the oral bioavailability of tenofovir disoproxil fumarate (TDF), an anti-HIV drug. Niosomes were formulated by conventional thin film hydration technique with different molar ratios of surfactant, cholesterol, and dicetyl phosphate. The formulated niosomes were found spherical in shape, ranging from 2.95 μm to 10.91 μm in size. Vesicles with 1 : 1 : 0.1 ratios of surfactant : cholesterol : dicetyl phosphate with each grade of span were found to have higher entrapment efficiencies, which were further selected for in vitro and in vivo studies. Vesicles formulated with sorbitan monostearate were found to have maximum drug release (99.091%) at the end of 24 hours and followed zero order release kinetics. The results of in vivo study revealed that the niosomes significantly enhanced the oral bioavailability of TDF in rats after a dose of 95 mg/kg. The average relative bioavailability of niosomes in relation to plane drug solution was found to be 2.58, indicating more than twofold increase in oral bioavailability of TDF. Significant increase in mean residential time (MRT) was also found, reflecting release retarding efficacy of the vesicles. In conclusion, niosomes could be a promising delivery for TDF with improved oral bioavailability and prolonged release profiles.